Fluorescent in-situ hybridization (FISH) for BCR/ABL in chronic myeloid leukemia after bone marrow transplantation - Chauffaille, Maria de Lourdes Lopes Ferrari; Oliveira, José Salvador Rodrigues; Romeo, Maura; Kerbauy, José (São Paulo Medical Journal, 2001)
CONTEXT: Identification of Philadelphia chromosome or BCR/ABL gene rearrangement in chronic myeloid leukemia is important at diagnosis as well as after treatment. OBJECTIVE: To compare the results of karyotyping using fluorescent in-situ hybridization (FISH) upon diagnosis and 1 year after bone marrow transplantation in 12 patients. TYPE OF STUDY: Diagnostic test and residual disease detection. SETTING: Hematology and Hemotherapy Department, Federal University of São Paulo/Escola Paulista de Medicina, São Paulo, Brazil. SAMPLE: 12 patients with chronic myeloid leukemia at diagnosis and 1 year after bone marrow transplantation. DIAGNOSTIC TEST: Karyotyping was done in the usual way and the BCR/ABL gene-specific probe was used for FISH. MAIN MEASUREMENTS: Disease at diagnosis and residual. RESULTS: At diagnosis, 10 patients presented t(9;22)(q34.1;q11) as well as positive FISH. Two cases did not have metaphases but FISH was positive. After bone marrow transplantation, 8 patients presented normal karyotype, 1 had persistence of identifiable Philadelphia chromosome and 3 had no metaphases. Two cases showed complete chimera and 2 had donor and host cells simultaneously. FISH was possible in all cases after bone marrow transplantation and confirmed the persistence of identifiable Philadelphia chromosome clone in one patient, and identified another that did not present metaphases for analysis. Cases that showed mixed chimera in karyotype were negative for BCR/ABL by FISH. CONCLUSION: The applicability of FISH is clear, particularly for residual disease detection. Classical and molecular cytogenetics are complementary methods.